Care Coordination: A Concept Analysis. Issue 12 (December 2021) - Anderson, Amanda; Hewner, Sharon
Abstract : ABSTRACT: Care coordination is both a well-known concept discussed in a wide range of multidisciplinary health care literature and a familiar nursing role in clinical practice; however, the definition of care coordination lacks role clarity across disciplines and within the nursing profession. Despite variations, defining factors of care coordination practice exist; however, role ambiguity limits the effective implementation of evidence-based care coordination in practice and policy. Following Walker and Avant's eight-step concept analysis method, we aim to further clarify care coordination as a concept and practice role and examine the value that nursing brings to its implementation. Abstract : The authors clarify care coordination as a concept and practice role and examine the value that nursing brings to its implementation.